Potential of Bacillus native to the Comarca Lagunera as a biofertilizer in the production of forage corn - García-de la Paz, Nery Cecilia; Gallegos-Robles, Miguel Ángel; González-Salas, Uriel; Rodríguez-Sifuentes, Lucio; Mendoza-Retana, Sarai Shesareli; Sánchez-Lucio, Roberto (Revista Mexicana de Ciencias Agrícolas, 2022)
Conventional agriculture is based on a production system dependent on a high use of synthetic inputs and today faces difficulties in maintaining acceptable levels in agricultural production due to the increase in costs and environmental pollution. A sustainable alternative to this problem is the use of plant growth-promoting bacteria, being a potential alternative when using them as biofertilizers. The objective of the work was to evaluate strains of Bacillus (Bacillus subtilis and Bacillus amyloquefaciens) native to the Lagunera region, testing their potential as biofertilizers in the cultivation of forage corn and evaluating the yield of dry matter. In the treatments, bacteria were applied individually, in combination with each other and with 50% of the recommended dose of chemical fertilizer, the variables evaluated were: leaf area, leaf weight, green corncob weight, cane weight, green corncob diameter, green corncob length, dry matter yield, root volume displacement, fresh root weight and dry root weight. Dry matter yield in Bacillus treatments did not show statistically significant differences compared to the chemical control, but bacterial treatments were numerically better. In the same way, an increase in root mass was observed in these treatments, so their use is considered as a viable alternative to replace chemical fertilizer.
Keywords: dry matter; PGPB; root mass